2021
DOI: 10.1038/s41467-021-25360-6
|View full text |Cite
|
Sign up to set email alerts
|

Microbial production of megadalton titin yields fibers with advantageous mechanical properties

Abstract: Manmade high-performance polymers are typically non-biodegradable and derived from petroleum feedstock through energy intensive processes involving toxic solvents and byproducts. While engineered microbes have been used for renewable production of many small molecules, direct microbial synthesis of high-performance polymeric materials remains a major challenge. Here we engineer microbial production of megadalton muscle titin polymers yielding high-performance fibers that not only recapture highly desirable pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 80 publications
0
34
0
Order By: Relevance
“…There are also studies about characterizing individual proteins of interest: Bowen et al. ( 35 ) microbially produced high-performance titin polymers and used CD to examine the secondary structure and fold of the purified polymers. Balacescu et al.…”
Section: Resultsmentioning
confidence: 99%
“…There are also studies about characterizing individual proteins of interest: Bowen et al. ( 35 ) microbially produced high-performance titin polymers and used CD to examine the secondary structure and fold of the purified polymers. Balacescu et al.…”
Section: Resultsmentioning
confidence: 99%
“…We fused split Mfp5 fragments to three types of fiber proteins, including a recombinant spider silk 16xAAA (polyalanine) 9 , another amyloid-silk hybrid protein 16xKLV 10 , and a titin fragment Ig67-70 11 . These fiber materials use different molecular interaction mechanisms and form different sizes and portion of β-nanocrystals 10 , 11 . Bi-terminal fusion of split Mfp5 fragments enhanced fiber ultimate tensile strength by 65.5-139% for all three proteins (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These ECMs present a unique pattern combined with the isotropic and anisotropic surface. [55,59,71] Thus, it is inevitably necessary to fabricate a tissue-mimicking biomaterial to investigate the cell response to a dynamic surface change. This study found that the cells' aspect ratio and spreading area on the BMAF surfaces increased progressively with the BMAF orientation degree.…”
Section: Bmaf-induced Cell Cytoskeleton Reorganizationmentioning
confidence: 99%